Pengembangan Model Kurikulum Pendidikan Agama Islam (PAI) Menuju Masyarakat Ekonomi Asean (MEA) - Muhamad Tisna Nugraha (AT-TURATS, 2016)
Education reformation that slowly run makes the potential of islam education of institution that existed has not discover not only from the professionalism side of educators but also the lack abdorption of graduated student from islam education of institution. There is no balancing numbers out put of graduated student with the job opportunities every year. So that, the rejuvenation of currucullum in Islam education of institution has to be priority especially dealing with other south east country approading ASEAN Economic Community (MEA).Hope fully, curriculum development increases graduated competency that oriented to find a job become to create a job opprortunities. Curriculum is an education tool as the answer to needs and challenges not only as an instrument to achieve education purposes, but also as “The Heart of Education” in the process. There fore a good curriculum will become investation for better quality of education. Nevertheless a bad curriculum will produce worse quality of education.